Enhanced 3D localisation accuracy of body‐mounted miniature antennas using ultra‐wideband technology in line‐of‐sight scenarios. Issue 1 (12th October 2017) - Sharma, Manmohan; Alomainy, Akram; Parini, Clive
Abstract : This study presents experimental investigations on high‐precision localisation methods of body‐worn miniature antennas using ultra‐wideband (UWB) technology in line‐of‐sight conditions. Time of arrival data fusion and peak detection techniques are implemented to estimate the three‐dimensional (3D) location of the transmitting tags in terms of x, y, z Cartesian coordinates. Several pseudo‐dynamic experiments have been performed by moving the tag antenna in various directions and the precision with which these slight movements could be resolved has been presented. Some more complex localisation experiments have also been undertaken, which involved the tracking of two transmitter tags simultaneously. Excellent 3D localisation accuracy in the range of 1–4 cm has been achieved in various experiment settings. A novel approach for achieving subcentimetre 3D localisation accuracy from UWB technology has been proposed and demonstrated successfully. In this approach, the phase centre information of the antennas in a UWB localisation system is utilised in position estimation to drastically improve the accuracy of the localisation measurements to millimetre levels. By using this technique, the average localisation error has been reduced by 86, 31, and 72% for the x‐, y‐, and z‐ axis coordinates, respectively.